Growth of horticulture sector in India: Trends and prospects - JHA, GIRISH K; SURESH, A; PUNERA, BHOOPESH; SUPRIYA, P (The Indian Journal of Agricultural Sciences, 2019)
Horticulture sector is recognised to have the potential to raise the farm income, provide livelihood security and earn foreign exchange. However, focused policy interventions are needed to realise the potential of the sector. The study examines the trends of the horticultural sector in India and identifies the growth prospects. The consumption of selected fruits and vegetables has grown at a rate of 18-23% and 10-20% in rural areas during 1993-94 to 2011- 12, still the quantity consumed is less than the recommended dietary requirements. Out of the overall growth rate of 3.56 per cent in agriculture during 2000-2011, fruits and vegetable alone accounted for 19.2%. The share of high value crops in value of output of the agricultural sector is also on increase, both in absolute terms as well as in shares. Horticultural sector accounts for about 37% of the total exports of agricultural commodities, and the exports have recorded sustained rising trend. Across states, there is wide variation on the growth performance. The major concerns of the sector are improving the productivity through research and development, enhancing the share of value added products, geographical diversification of exports and enhancing the infrastructure including cold storage and rural roads. The public sector research needs to be strengthened factoring in the constraints of small holders who constitute the major producers.